2020
DOI: 10.1155/2020/8241509
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Analysis of NPR Anchorage Monitoring of Bedding Rock Landslide in Open‐Pit Mine

Abstract: Nanfen open-pit iron mine is the largest single open-pit mine in Asia. Because of the lag of the extension project, the section has slowly spread in the shape of "V," and disasters such as landslides occur frequently. In this study, first, the NPR anchor cable monitoring, which shows supernormal mechanical characteristics and can realize the monitoring and early warning target for the whole landslide process and early warning curve of bedding rock "2016-1101 landslide" in the lower wall of Nanfen open-pit mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A large number of scholars used numerical simulation methods combined with monitoring to conduct research on the stability of open pit slopes and used conventional GNSS, total station monitoring [27,28], etc. ere are few applications for InSAR (synthetic aperture radar jamming) obtaining mine surface deformation data but which is developing more rapidly today in other fields [29][30][31]…”
Section: Introductionmentioning
confidence: 99%
“…A large number of scholars used numerical simulation methods combined with monitoring to conduct research on the stability of open pit slopes and used conventional GNSS, total station monitoring [27,28], etc. ere are few applications for InSAR (synthetic aperture radar jamming) obtaining mine surface deformation data but which is developing more rapidly today in other fields [29][30][31]…”
Section: Introductionmentioning
confidence: 99%
“…In view of the limitation of traditional anchor cables with respect to mechanical properties and severe engineering environments, new anchor cables with extraordinary mechanical properties should be developed. Existing NPR anchor cables have solved the deformation problem of deep, soft rock roadways [20,21]. The deformation capacity increases to 3000-4000 mm, and the maximum constant resistance is 567.7-800 kN [22].…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [15,16] studied the settlement and deformation of an open-pit mine dump by combining field monitoring data and numerical simulations. Zhang et al [17] analyzed the anchor cable monitoring in the Nanfen open-pit mine and revealed the failure process of a bedding rock landslide and the stress evolution characteristics of negative Poisson's ratio (NPR) cables. Xu and Yan [18] used FLAC 3D to simulate the influence of excavation and blasting vibration on goaf stability.…”
Section: Introductionmentioning
confidence: 99%